Eileen Gray: a child of Japonism? - Starr, Ruth (Trinity College Dublin. Long Room Hub, 2008)
My interest is in Gray's lacquer work and the influences on that work in the context of nineteenth-century fashion of Japonisme. Gray (1878-1976) had an appreciation of the Japanese characteristics of lacquer - perhaps absorbed from private and public Irish collections of Japanese art. Gray also had a twenty-year working collaboration with Seizo Sugawara (1884-1937) from Jahoji, Japan - a town famous for its lacquer work. Sugawara was her most immediate contact with Japan, yet Sugawara's contribution has been sidelined in studies of Gray's lacquer work. I believe my research will add new insights to Gray as an artist, suggesting new interpretations of her work in the light of the previously overlooked influence of Japonisme and Sugawara on Gray.
Exhibited at the Glucksman Memorial Symposium on June 12th 2008
Keywords: Eileen Gray; Japonism; Art history; Lacquer work